Conflict Resolution Learning Model As A Strategic Effort in Building Peace Amidst Indonesia's Diversity - Laros Tuhuteru; Yanry Budianingsih; I Gusti Ngurah Santika; I Made Kartika; I Gede Sujana; Esto Bula Wiri Memang (Widya Accarya, 2023)
As a pluralistic country, peace still seems to be a mere wishful thinking. Because all this time conflicts that are rooted in pluralism have injured and damaged the peace that was actually agreed upon by the founders of the nation. The purpose of this research was to find out the conflict resolution learning model as a strategic effort in building peace in the midst of Indonesia's diversity. The method used in this research was a library method or approach. Data collection techniques in this research used documentation and literature. The data obtained were then analyzed in depth and presented descriptively. The results of this research indicated that strategic efforts to build peace in the midst of Indonesia's diversity are carried out by educational institutions through the application of conflict resolution learning models. The application of the conflict resolution learning model aims to train students' skills in solving critical problems, communication, and interpersonal skills better. Conflict resolution methods can optimize student competence, especially training social values, social sensitivity and problem solving skills. In relation to the diversity of the Indonesian nation, there is a significant influence from the use of conflict resolution learning models on students' multicultural attitudes. The multicultural attitude of students who take part in learning with the conflict resolution learning model obtains good results.